The Comparison Between Indonesia’s and Singapore’s Digital Diplomacy Through the Instagram Account of @wonderfulindonesia and @visit_singapore - soetiman, gabrian cornelis; krishnamurti, indra v.a; sharief, fadhlanti (LIAISON JOURNAL OF BEST, 2024)
In the last couple of years, digital diplomacy has become a relevant subject in the field of international relation. Other than that, nations around the world are beginning to see the importance of digital diplomacy activities towards themselves. In today’s world, digital diplomacy can be done through social media, mass media, and conferences through the digital space. In this research paper, the author will be focusing on the comparison of digital diplomacy activities conducted by Indonesia and Singapore on Instagram through the account of @wonderfulindonesia and @visit_singapore. From both accounts, it can be seen that Indonesia and Singapore have a different way to promote their nation. Furthermore, both nation’s Instagram account is aligned with their respective nation branding of “Wonderful Indonesia” and “Passion Made Possible”. After observing their Instagram account, it can be seen that both nations focused on building an image through each of their strengths. Furthermore, both nations have put a lot of effort to ensure that their Instagram account remain relevant in the international community. Other differences and similarities will explore in this research paper. Keywords: Digital diplomacy, nation branding, Indonesia, Singapore, @wonderfulindonesia, @visit_singapore, social media, Instagram